2011
DOI: 10.1176/ps.62.9.pss6209_1013
|View full text |Cite
|
Sign up to set email alerts
|

Career Satisfaction of Psychiatrists

Abstract: The results of this study highlight the need for policy makers and health care administrators to develop specific strategies to increase career satisfaction, which in return may help alleviate the shortage of psychiatrists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…Previous studies of physician satisfaction found correlations between age and satisfaction. Although two studies found that older clinicians reported higher satisfaction than younger clinicians [4, 6] Leigh et al [7] reported a nonlinear relationship between physician age and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of physician satisfaction found correlations between age and satisfaction. Although two studies found that older clinicians reported higher satisfaction than younger clinicians [4, 6] Leigh et al [7] reported a nonlinear relationship between physician age and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Pathman et al [4] reported that older generalist and specialist physicians reported higher satisfaction than younger physicians for 8 of 10 studied aspects. Similarly, DeMello & Deshpande [6] reported higher satisfaction among older psychiatrists compared to younger ones. However, Leigh et al [7] reported a nonlinear relationship between physician age and satisfaction; the youngest and oldest physicians had the highest satisfaction.…”
Section: Introductionmentioning
confidence: 95%
“…This finding is intuitive and has been replicated for other specialties in this survey, including hospitalists, 18 pediatricians, 19 and psychiatrists. 20 The correlation matrix in Table 3 shows that high-quality care was negatively correlated with Medicare patients (À0.12, P < .05). Caring for our nation's elderly and Medicare patients was a significant issue throughout the early 2000s, spawning countless advocacy groups, legislative efforts, and political debates.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent studies of physician satisfaction using HSC data have flagged significant relationships at P .07 and P .10. [18][19][20] For consistency's sake, the higher alpha () is used here. Table 1 shows that obstetrician-gynecologists were largely satisfied with their careers in medicine; 45.2% were ''somewhat satisfied'' and 35.2% were ''very satisfied.''…”
Section: Discussionmentioning
confidence: 99%
“…A study of career satisfaction of psychiatrists reported that "adequate time with a patient had significant positive impact on career satisfaction" (Demello & Deshpande, 2011). It is a dilemma worthy of Solomon's attention-or preferably, systematic remedies.…”
Section: How Will Ecps Make Their Choices?mentioning
confidence: 99%